Existence of Solutions to a Class of Semilinear Elliptic Problem with Nonlinear Singular Terms and Variable Exponent. (13th June 2016) - Chu, Ying; Gao, Yanchao; Gao, Wenjie
Abstract : The authors of this paper prove the existence and regularity results for the homogeneous Dirichlet boundary value problem to the equation - d i v ( M ( x ) ∇ u n ) = f ( x ) / u α ( x ) with f ∈ L m ( Ω ) ( m ⩾ 1 ) and α ( x ) > 0 . The results show the dependence of the summability of f in some Lebesgue spaces and on the values of α ( x ) .